2014
DOI: 10.4172/2165-8048.1000150
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diseases of the Digestive System: Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome (IBS) is a very prevalent and high incident disease. As the great majority of functional diseases, it is female predominant and leads to serious damage to the quality of life. Its pathophysiology is complex, which pushes the specialists to study it even more deeply, in order to find the most suitable way to diagnose and treat it. Depending of the clinical presentation, different drugs can be used, although we are still missing the magic bullet to relieve our patient's complaints. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…[11] IBS is more common in women than men. [21213] SEPAHAN systematic review also showed the greater prevalence in women than men. [9]…”
Section: Introductionmentioning
confidence: 99%
“…[11] IBS is more common in women than men. [21213] SEPAHAN systematic review also showed the greater prevalence in women than men. [9]…”
Section: Introductionmentioning
confidence: 99%